Childhood Overweight/Obesity amidst Migration, Socioeconomic Factors, and Obesogenic Behaviors: Insights from the Growing Up in New Zealand Study - Mehdi Rahimi; Allen Bartley; Ladan Hashemi (Hindawi Limited, 2023)
Research on migration as a risk factor for obesity has produced inconsistent findings. Potential influence of migration as a social determinant of obesity has not been previously explored in New Zealand (NZ) as a migrant receiving country. This study aimed to investigate the link between maternal migration status and residential duration and childhood overweight/obesity risk in NZ, considering sociodemographic characteristics and obesogenic behaviors. Data on 5,506 4- to 5-year-old children and their mothers were taken from a large and nationally representative cohort study in NZ (the Growing Up in NZ Study). Multivariable logistic regression analyses were conducted to examine the association between maternal migration status, maternal residential duration, and child's overweight/obesity risk and the risk of adopting obesogenic behaviors independent of socioeconomic influences. A lower proportion of children of foreign-born mothers presented with overweight/obesity (26%) at age 5 years compared with children of NZ-born mothers (29.6%) (adjusted odds ratio (AOR) 0.85, 95% confidence interval (CI) (0.74, 0.98)). Maternal residential duration had no association with children's weight status among migrant families. Regarding obesogenic behaviors, the findings were mixed with children of foreign-born mothers having lower odds of consuming fast food (AOR 0.77, 95% CI (0.65, 0.91)) and soft drinks (AOR 0.87, 95% CI (0.76, 0.99)); however, they had higher odds of having inadequate sleep duration (AOR 2.25, 95% CI (1.85, 2.73)). The lower prevalence of overweight/obesity and lower odds of consuming fast foods and soft drinks among children of foreign-born mothers indicate potential protective factors within migrant families. However, the increased likelihood of inadequate sleep duration highlights an area of concern that warrants further attention and intervention. The findings emphasize the importance of considering diverse social determinants of health and specific risk factors when developing targeted interventions to address childhood overweight/obesity.